2017
DOI: 10.1186/s12902-017-0218-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric testing of a theory-based tool to measure self-care in diabetes patients: the Self-Care of Diabetes Inventory

Abstract: BackgroundSelf-care is essential for patients with diabetes mellitus. Both clinicians and researchers must be able to assess the quality of that self-care. Available tools have various limitations and none are theoretically based. The aims of this study were to develop and to test the psychometric properties of a new instrument based on the middle range-theory of self-care of chronic illness: the Self-Care of Diabetes Inventory (SCODI).MethodsForty SCODI items (5 point Likert type scale) were developed based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
124
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 80 publications
(140 citation statements)
references
References 38 publications
11
124
1
4
Order By: Relevance
“…The analysis showed a hierarchical structure for two scales composed by two factors for each scale: the self‐care maintenance for patient and caregiver and the self‐care management for patient and caregiver. As in some previous Italian studies, factor analysis revealed similar results …”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The analysis showed a hierarchical structure for two scales composed by two factors for each scale: the self‐care maintenance for patient and caregiver and the self‐care management for patient and caregiver. As in some previous Italian studies, factor analysis revealed similar results …”
Section: Discussionsupporting
confidence: 88%
“…Unlike other studies conducted in Italy on chronic populations with different clinical conditions, the level of self‐care of the ostomy patients and their caregivers was good . This result probably reflects the high support to self‐care performed by stomatherapist nurses.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations